Negative electrode for lithium secondary battery and method for producing same

A two-layered negative electrode structure with aligned natural and artificial graphite in lithium secondary batteries addresses adhesion and stability issues, improving life characteristics and energy density.

JP2025503069AActive Publication Date: 2025-01-30LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024543247
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-23
Filing Date
2023-10-25
Publication Date
2025-01-30
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face challenges with graphite-based negative electrodes, such as poor adhesion to collectors, low life characteristics, and inadequate impact resistance due to the use of mixed graphite or crystalline carbon materials.

Method used

A lithium secondary battery design featuring a two-layered negative electrode structure, where the first layer contains a mixture of natural and artificial graphite, with a specific ratio of artificial graphite exceeding 50% by weight, and both layers are aligned at a predetermined angle using a magnetic field during manufacturing to enhance adhesion and stability.

Benefits of technology

The proposed structure improves the adhesion between the negative electrode and the collector, enhances the battery's life characteristics, and increases energy density and output performance by optimizing the composition and alignment of graphite particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503069000001_ABST
    Figure 2025503069000001_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode for a lithium secondary battery and a manufacturing method thereof. The negative electrode has a structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially laminated on a negative electrode current collector, the first negative electrode active layer contains artificial graphite and natural graphite as a carbon-based negative electrode active material, and the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first negative electrode active layer is 0.01 to 0.01. 1st By adjusting the content of the carbon black and the artificial graphite within a specific range, the adhesive strength between the negative electrode active layer and the negative electrode current collector is excellent, and the secondary battery including the same has an excellent life.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0183044 dated December 23, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a negative electrode for a lithium secondary battery and a method for producing the same. [Background technology]

[0003] 2. Description of the Related Art In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.

[0004] Such secondary batteries are power generating elements capable of being charged and discharged and have a laminated structure of a positive electrode / separator / negative electrode. In general, the positive electrode contains a lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based active material such as graphite. During charging, lithium ions released from the positive electrode are absorbed into the carbon-based active material of the negative electrode, and during discharging, the lithium ions contained in the carbon-based active material are absorbed into the lithium metal oxide of the positive electrode, thereby allowing repeated charging and discharging.

[0005] On the other hand, as the negative electrode active material used in the negative electrode, amorphous carbon or crystalline carbon is used, and among them, crystalline carbon is mainly used because of its high capacity. Such crystalline carbon includes graphite-based carbon such as natural graphite and artificial graphite.

[0006] The graphite carbon has different characteristics depending on the type. For example, natural graphite shows high output and excellent adhesion to the current collector, but is relatively lacking in resistance and life characteristics compared to artificial graphite. However, artificial graphite has a low content of surface defects and functional groups, so it has a weak adhesion to the current collector. When propylene carbonate (PC) is mixed into the electrolyte to improve low-temperature performance, the propylene carbonate exfoliates and destroys each layer that constitutes the interlayer structure of the graphite.

[0007] For this reason, there have been attempts to use mixed graphite as the negative electrode active material of lithium secondary batteries in order to combine the properties of each type appropriately and utilize the advantages of each. However, in the case of such mixed graphite, the adhesive strength to the current collector is reduced, and there are limitations in terms of life characteristics and impact stability, which make it difficult to reach a satisfactory level.

[0008] Therefore, it is necessary to develop a new technology that can utilize the advantages of graphite-based carbon as a negative electrode active material while solving the disadvantages associated with it. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a negative electrode for a lithium secondary battery which contains graphite-based carbon as a negative electrode active material and yet has high adhesive strength to a current collector and excellent battery performance such as life characteristics, and a method for producing the same. [Means for solving the problem]

[0010] To solve the above-mentioned problems, In one embodiment, the present invention comprises: a negative electrode current collector; a first negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a first carbon-based negative electrode active material; and a second negative electrode active layer provided on the first negative electrode active layer and containing a second carbon-based negative electrode active material; The first carbon-based negative electrode active material includes natural graphite and artificial graphite, The first negative electrode active layer and the second negative electrode active layer each provide a negative electrode for a lithium secondary battery, in which the degree of alignment (OI) of the carbon-based negative electrode active material represented by the following formula 1 is 0.1 to 0.9:

[0011] [Formula 1] OI=I 004 / I 110

[0012] In formula 1, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0013] In this case, the content of the artificial graphite contained in the first carbon-based negative electrode active material may exceed 50 wt % based on the total weight of the first carbon-based negative electrode active material.

[0014] In addition, the second carbon-based negative electrode active material may include artificial graphite.

[0015] In addition, the degree of alignment (OI) of the second carbon-based negative electrode active material 2nd ) is the degree of alignment (OI) of the first carbon-based negative electrode active material 1st ) may have a ratio of 10% to 100%.

[0016] The above-mentioned artificial graphite may be scaly particles, and the natural graphite may be spherical particles. The average particle size of the artificial graphite may be 5 μm to 20 μm, and the average particle size of the natural graphite may be 15 μm to 25 μm, and the average particle size of the artificial graphite may be smaller than the average particle size of the natural graphite.

[0017] Meanwhile, the total thickness of the first negative electrode active layer and the second negative electrode active layer may be 50 μm to 300 μm.

[0018] Here, the average thickness of the first negative electrode active layer may be 10% to 100% of the average thickness of the second negative electrode active layer.

[0019] In one embodiment, the present invention further comprises: Simultaneously applying a first negative electrode slurry including a first carbon-based negative electrode active material and a second negative electrode slurry including a second carbon-based negative electrode active material onto a negative electrode current collector; applying a magnetic field to the applied first and second negative electrode slurries; and drying the first and second negative electrode slurries to which the magnetic field is applied to form a first and second negative electrode active layer, The first carbon-based negative electrode active material includes natural graphite and artificial graphite, The first and second negative electrode active layers each have an alignment degree (OI) of 0.1 to 0.9 of the carbon-based negative electrode active material represented by the following formula 1:

[0020] [Formula 1] OI=I 004 / I 110

[0021] In formula 1, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0022] At this time, in the step of applying the magnetic field, a magnetic field of 2,000 G to 6,000 G may be applied.

[0023] The step of applying the magnetic field may be performed for 5 to 60 seconds.

[0024] In addition, forming the first and second negative electrode active layers may include drying the first and second negative electrode slurries, and rolling the dried first and second negative electrode slurries. Effect of the Invention

[0025] The negative electrode for a lithium secondary battery according to the present invention has a structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially laminated on a negative electrode current collector, the first negative electrode active layer contains artificial graphite and natural graphite as a carbon-based negative electrode active material, and the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first negative electrode active layer is 0.01 to 0.01. 1st By adjusting the content of the carbon black and the artificial graphite within a specific range, the adhesive strength between the negative electrode active layer and the negative electrode current collector is excellent, and the secondary battery including the same has an excellent life. [Brief description of the drawings]

[0026] [Figure 1] 4 is a scanning electron microscope image showing the shape of artificial graphite in the carbon-based negative electrode active material according to the present invention; [Diagram 2] 3 is a scanning electron microscope image showing the shape of natural graphite in the carbon-based negative electrode active material according to the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Since the present invention can be modified in various ways and has various embodiments, specific embodiments will be described in detail in the detailed description.

[0028] However, this is not intended to limit the invention to any particular embodiment, but it should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.

[0029] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and may be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0030] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.

[0031] In the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of a defined component based on the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite based on the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.

[0032] The present invention will now be described in more detail.

[0033] <Negative electrodes for lithium secondary batteries> In one embodiment, the present invention comprises: a negative electrode current collector; a first negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a first carbon-based negative electrode active material; and a second negative electrode active layer provided on the first negative electrode active layer and containing a second carbon-based negative electrode active material; The first carbon-based negative electrode active material includes natural graphite and artificial graphite, The first negative electrode active layer and the second negative electrode active layer each provide a negative electrode for a lithium secondary battery, in which the degree of alignment (OI) of the carbon-based negative electrode active material represented by the following formula 1 is 0.1 to 0.9:

[0034] [Formula 1] OI=I 004 / I 110

[0035] In formula 1, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0036] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode active layer including a carbon-based active material on at least one surface of a negative electrode current collector. The negative electrode active layer is a layer that realizes the electrical activity of the negative electrode, and is prepared by coating both surfaces of the electrode current collector with an electrode slurry including a negative electrode active material that realizes an electrochemical oxidation-reduction reaction during charging and discharging of the battery, and then drying and rolling the coating.

[0037] In this case, the negative electrode active layer includes a carbon-based active material as a negative electrode active material to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the battery. Specifically, the carbon-based active material means a material mainly composed of carbon atoms, and the carbon-based active material may include graphite-based carbon. The graphite-based carbon may include at least one of natural graphite and artificial graphite.

[0038] The graphite carbon has a powder form, and the powder may be composed of particles having a shape such as a spherical shape, a scaly shape, an irregular shape, etc. Here, "scaly particles" refers to particles having a thin plate shape, and the surface of the particles may have an average aspect ratio of 1:2 to 1:20.

[0039] As one example, synthetic graphite may include flake particles, while natural graphite may include spherical particles.

[0040] In this case, the artificial graphite preferably has a structure in which a plurality of scale-like particles are aggregated to form a spherical granule, as shown in FIG. 1. Moreover, one graphite granule may be formed by aggregating 2 to 100, preferably 3 to 20, scale-like graphite particles. The present invention can improve the energy density by controlling the particle shape of the artificial graphite as described above. Moreover, since the specific surface area relative to the average size of the artificial graphite can be increased, the adhesive strength to the negative electrode current collector can be improved.

[0041] In addition, the natural graphite may include spherical particles as shown in FIG. 2, and may have a sphericity of 0.75 or more, for example, 0.75 to 1.0, 0.75 to 0.95, 0.8 to 0.95, or 0.90 to 0.99. Here, the "sphericity" may refer to the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle when the carbon-based negative electrode active material is projected onto a two-dimensional particle, and when the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer or by analyzing a particle image through scanning electron microscope (SEM) photography. The present invention has the advantages of realizing a shape of natural graphite close to a sphere, thereby realizing a high electrical conductivity of the negative electrode active layer, thereby improving the capacity of the battery, and increasing the specific surface area of ​​the particles, thereby improving the adhesive force between the negative electrode active layer and the current collector.

[0042] The graphite-based carbon may be controlled so that the size thereof falls within a predetermined range. Specifically, the artificial graphite may be 5 μm to 20 μm, the average particle size of the natural graphite may be 15 μm to 25 μm, and the average particle size of the natural graphite may be larger than the average particle size of the artificial graphite. Here, the average particle size of the artificial graphite may mean the average size of a granule formed by aggregating a plurality of scale-like particles.

[0043] Specifically, the average particle size of the artificial graphite (D 50 ) may be 5 μm to 15 μm, 5 μm to 12 μm, 10 μm to 20 μm, 15 μm to 20 μm, 12 μm to 18 μm, or 8 μm to 14 μm, and the average particle size (D 50 ) may be 15 μm to 20 μm, 20 μm to 25 μm, 18 μm to 23 μm, or 21 μm to 25 μm.

[0044] As an example, the average particle size of artificial graphite may be 8 μm to 10 μm, and the average particle size of natural graphite may be 18 μm to 20 μm.

[0045] If the minimum particle size of the artificial graphite and natural graphite is less than 5 μm and 15 μm, respectively, a large amount of binder is required due to the increase in the number of particles per unit volume, which may result in a decrease in the electrical properties of the negative electrode, a large volume change rate due to contraction and expansion of the negative electrode active material during charging and discharging of the battery, and a decrease in the durability of the negative electrode active layer. On the other hand, if the maximum particle size of the artificial graphite and natural graphite is more than 20 μm and 25 μm, respectively, the expansion becomes intense, and the adhesion between the particles and the adhesion between the particles and the current collector decreases with repeated charging and discharging, which may result in a significant decrease in cycle characteristics.

[0046] In addition, the present invention may realize a structure in which the artificial graphite is densely packed between a plurality of natural graphite particles contained in the negative electrode active layer by controlling the average particle size of the artificial graphite to be smaller than that of the natural graphite. Due to this structure, the negative electrode of the present invention may have a reduced resistance of the negative electrode active layer, while the energy density of the negative electrode may be increased, thereby improving output performance.

[0047] Meanwhile, the negative electrode active layer may have a structure in which two individual layers are laminated. Specifically, the negative electrode according to the present invention may have a structure in which a first negative electrode active layer is provided on a negative electrode current collector, and a second negative electrode active layer is provided on the first negative electrode active layer. The present invention realizes a two-layer structure for the negative electrode active layer, thereby making it easier to control the physical properties required for each region of the negative electrode active layer. That is, the negative electrode active layer according to the present invention has an advantage in that it realizes a higher adhesive force between the active layer and the negative electrode current collector in a region adjacent to the negative electrode current collector, and realizes a higher density of energy generated by the electrochemical reaction in a region adjacent to the active layer surface where the electrochemical reaction occurs at a high density.

[0048] For this reason, the first and second negative electrode active layers constituting the negative electrode active layer may have different compositions.

[0049] Specifically, the first negative electrode active layer includes a first carbon-based negative electrode active material, and the second negative electrode active layer includes a second carbon-based negative electrode active material, in which the first carbon-based active material and the second carbon-based active material include at least one type of graphite-based carbon selected from natural graphite and artificial graphite, and the type and content / content ratio of the graphite-based carbon included in each carbon-based active material may be different.

[0050] As one example, the first carbon-based negative electrode active material may include natural graphite and artificial graphite, and the second carbon-based negative electrode active material may include only artificial graphite.

[0051] Here, the first carbon-based negative electrode active material may contain artificial graphite in an amount greater than 50 wt% based on the total weight of the first carbon-based negative electrode active material, and more specifically, may contain artificial graphite in an amount of 60 wt% or more, 65 wt% or more, 70 wt% or more, 75 wt% or more, 80 wt% or more, 60 wt% to 99 wt%, 60 wt% to 90 wt%, 65 wt% to 95 wt%, 70 wt% to 95 wt%, 75 wt% to 95 wt%, or 75 wt% to 90 wt% based on the total weight of the first carbon-based negative electrode active material.

[0052] In the present invention, by controlling the content of artificial graphite in the first carbon-based negative electrode active material contained in the first negative electrode active layer to fall within the above range, the electrical resistance in the region adjacent to the negative electrode current collector can be reduced, thereby improving the high-output performance of the negative electrode and suppressing deterioration of the negative electrode active layer when the secondary battery is charged and discharged for a long period of time.

[0053] Furthermore, in the negative electrode according to the present invention, the first carbon-based negative electrode active material and the second carbon-based negative electrode active material contained in the first negative electrode active layer and the second negative electrode active layer may be oriented at a predetermined angle. Here, "the carbon-based negative electrode active material is oriented (or aligned)" may mean that a specific crystal plane showing the planar molecular structure of the carbon-based negative electrode active material, specifically, graphite-based carbon, is arranged to have a predetermined angle / inclination with respect to the negative electrode current collector. This is different from the specific plane of the graphite-based carbon particles themselves being arranged to have a predetermined angle / inclination with respect to the negative electrode current collector.

[0054] In the present invention, the carbon-based negative active material, i.e., graphite-based carbon, contained in the negative active layer may have a crystal plane aligned nearly perpendicular to the negative current collector, specifically, may be aligned to have an angle of 60° or more, 70° or more, 70 to 90°, 80 to 90°, 65 to 85°, or 70 to 85° to the negative current collector. The degree of alignment of such a carbon-based negative active material (e.g., graphite-based carbon) may be determined by a crystal plane analysis of the carbon-based active material contained in the negative active layer.

[0055] As one example, in the negative electrode active layer, the carbon-based active material is aligned in a certain direction with respect to the negative electrode current collector, and when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD), the average degree of alignment of the carbon-based active material represented by the following formula 1 may satisfy 0.1 to 0.9:

[0056] [Formula 1] OI=I 004 / I 110

[0057] In formula 1, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0058] The above formula 1 can be an index showing the degree to which the crystal structure of the carbon-based active material, i.e., graphite-based carbon, is aligned in a certain direction, specifically, with respect to the surface of the negative electrode current collector, during X-ray diffraction measurement. More specifically, the negative electrode active layer shows peaks of 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° for the carbon-based active material graphite during X-ray diffraction measurement. These represent the (0,0,2) plane, (1,0,0) plane, (1,0,1)R plane, (1,0,1)H plane, (0,0,4) plane, and (1,1,0) plane of graphite, respectively. In addition, the peak appearing at 2θ=43.4±0.2° may be due to an overlap of the (1,0,1)R plane of the carbon-based active material and the peak corresponding to the (1,1,1) plane of the current collector, for example, copper (Cu).

[0059] Among these, the degree of alignment (OI) of the carbon-based active material (i.e., graphite-based carbon) can be measured by the area ratio of the peak at 2θ=54.7±0.2° indicating the (0,0,4) plane and the peak at 2θ=77.5±0.2° indicating the (1,1,0) plane, specifically, the area ratio obtained by integrating the intensity of the above peaks. Here, the peak at 2θ=54.7±0.2° is a peak indicating the (0,0,4) plane of the graphite crystal planes that has a tilt with respect to the negative electrode current collector, so the degree of alignment (OI) closer to 0 means that the tilt with respect to the surface of the negative electrode current collector is closer to 90°, and the larger the value, the closer the tilt with respect to the surface of the negative electrode current collector is to 0° or 180°.

[0060] In addition, in the negative electrode of the present invention, the carbon-based active materials contained in the first and second negative active layers may be aligned to have a predetermined direction with respect to the negative current collector, and thus the carbon-based active materials contained in the first and second negative active layers may have different degrees of alignment (OI). Specifically, the first carbon-based active material contained in the first negative active layer may have a higher degree of alignment (OI) than the second carbon-based active material contained in the second negative active layer.

[0061] As an example, the degree of alignment (OI) of the second carbon-based active material contained in the second negative electrode active layer 2nd ) is the degree of alignment (OI) of the carbon-based active material contained in the first negative electrode active layer. 1st ) may have a ratio of 10% to 100%, and more specifically may have a ratio of 50% to 99%, 60% to 99%, 70% to 99%, 80% to 99%, or 60% to 85%.

[0062] In this case, the degree of alignment (OI) of the carbon-based active material contained in the second negative electrode active layer 2nd ) may be 0.1 to 0.9, and more specifically may be 0.1 to 0.7, 0.1 to 0.5, 0.2 to 0.6, 0.4 to 0.7, 0.3 to 0.5, or 0.1 to 0.4.

[0063] In the negative electrode according to the present invention, by controlling the degree of alignment (OI) of the carbon-based active material contained in each of the first and second negative electrode active layers as described above, the electrolyte and lithium mobility in the second negative electrode active layer can be improved, the electrode capacity can be increased, and the adhesion between the first negative electrode active layer and the negative electrode current collector can be further strengthened.

[0064] Furthermore, in the second negative electrode active layer, the second carbon-based negative electrode active material is aligned to the negative electrode current collector at a certain angle / inclination, and may exhibit a predetermined color difference value when any three points on the surface are analyzed with a CIE color difference meter.

[0065] As one example, the second negative electrode active layer may have an L* value of 40 or less when analyzed with a CIE color difference meter for any three points located on the surface, and a ΔL* value of less than 10. More specifically, the second negative electrode active layer may have an L* value of 30 to 40, 30 to 35, 32 to 35, or 31 to 34.5 when analyzed with a CIE color difference meter for any three points located on the surface, and a ΔL* value of less than 8, less than 5, less than 3, or less than 2.

[0066] The L* value is an element indicating the brightness of a color, and L*=0 indicates black, and L*=100 indicates white. The negative electrode active layer in the present invention contains graphite as a carbon-based negative electrode active material as a main component and is black, so it has an L* of 30 or more, and the graphite contained in the negative electrode active layer is uniformly crystalline oriented with respect to the negative electrode current collector, so that the L* deviation (i.e., ΔL*) at multiple points can be low.

[0067] Meanwhile, the total thickness of the first negative electrode active layer and the second negative electrode active layer may be 50 μm to 300 μm, specifically 50 μm to 250 μm, 100 μm to 250 μm, or 100 μm to 200 μm. By adjusting the total thickness of the negative electrode active layers to the above range, the present invention can not only increase the energy density of the electrode, but also uniformly control the degree of alignment of the carbon-based active material contained in the negative electrode active layers.

[0068] In addition, the average thickness of the first negative electrode active layer may be 10% to 100% of the average thickness of the second negative electrode active layer, specifically, 10% to 50%, 10% to 40%, 30% to 50%, 40% to 70%, 50% to 99%, 60% to 99%, 70% to 99%, 60% to 85%, or 80% to 100% of the average thickness of the second negative electrode active layer. By adjusting the average thickness of the first negative electrode active layer to the above range, the present invention can easily increase the charge / discharge capacity and output that the entire negative electrode active layer can realize while improving the adhesive strength between the negative electrode current collector and the negative electrode active layer.

[0069] Meanwhile, the first and second negative electrode active layers according to the present invention may further include a silicon-based negative electrode active material in addition to the carbon-based negative electrode active material.

[0070] Such silicon-based negative electrode active materials may include silicon-based materials containing at least one of silicon (Si), silicon carbide (SiC), silicon monoxide (SiO), and silicon dioxide (SiO2). Here, when silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or composited and included in the negative electrode active layer, they are called silicon oxide (SiO q , where 0.8≦q≦2.5).

[0071] The silicon-based negative electrode active material may be contained in an amount of 1 to 20% by weight based on the total weight of the negative electrode active material contained in each negative electrode active layer, and specifically, may be contained in an amount of 1 to 9 parts by weight, 3 to 7 parts by weight, 5 to 15 parts by weight, 11 to 19 parts by weight, or 13 to 17 parts by weight based on the total weight of the negative electrode active material.

[0072] By adjusting the content of the silicon-based negative electrode active material within the above range, the present invention can minimize the volume change rate of the negative electrode active layer due to charging and discharging, and at the same time, can improve the charge capacity per unit mass while reducing the amount of lithium consumption and irreversible capacity loss during the initial charging and discharging of the battery.

[0073] Furthermore, the first negative electrode active layer and the second negative electrode active layer according to the present invention may further selectively contain, in addition to the negative electrode active material, a conductive material, a binder, other additives, and the like, as necessary.

[0074] The conductive material may include one or more of, but is not limited to, carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like.

[0075] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductive material.

[0076] At this time, the content of the conductive material may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the conductive material within the above range, the present invention can prevent the negative electrode resistance from increasing due to a low content of conductive material, resulting in a decrease in charge capacity. In addition, it can prevent problems such as a decrease in the content of the negative electrode active material due to an excessive amount of conductive material, resulting in a decrease in charge capacity, or a decrease in rapid charge characteristics due to an increase in the loading amount of the negative electrode active layer.

[0077] The binder is a component that aids in bonding between the active material and the conductive material and between the active material and the current collector, and may be suitably used within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more selected from the group consisting of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, and fluororubber.

[0078] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.

[0079] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 μm to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.

[0080] <Lithium secondary battery> In one embodiment, the present invention further comprises: There is provided a lithium secondary battery comprising an electrode assembly including a positive electrode, the negative electrode of the present invention described above, and a separator disposed between the positive electrode and the negative electrode.

[0081] The lithium secondary battery according to the present invention includes an electrode assembly in which a plurality of positive electrodes, a separator, and a negative electrode are sequentially arranged, and an electrolyte composition in which a lithium salt and an electrolyte additive are dissolved in a non-aqueous organic solvent. The lithium secondary battery has a structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially laminated on a negative electrode current collector, the first negative electrode active layer includes artificial graphite and natural graphite as carbon-based negative electrode active materials, and the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first negative electrode active layer is 100%. 1st The negative electrode of the present invention includes a negative electrode having a specific content of the anode active layer and the anode current collector, and the content of the anode active layer and the anode current collector is adjusted to a specific range. As a result, the lithium secondary battery has an excellent adhesive strength between the anode active layer and the anode current collector, and the secondary battery including the anode has an excellent life.

[0082] The negative electrode has the same configuration as described above, and therefore a detailed description thereof will be omitted.

[0083] The positive electrode includes a positive electrode active layer prepared by applying a slurry containing a positive electrode active material onto a positive electrode current collector, followed by drying and pressing, and may further include a conductive material, a binder, other additives, and the like as necessary.

[0084] The positive electrode active material is a material capable of electrochemically reacting on the positive electrode current collector, and may include one or more of the lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 capable of reversibly intercalating and deintercalating lithium ions:

[0085] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2

[0086] [Chemical formula 2] LiM 2 p Mn q P r O4

[0087] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつ、y+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is 0.05≦p≦1.0, q is 1-p or 2-p; r is 0 or 1.

[0088] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 above are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, have the advantage of being capable of stably supplying high capacity and / or high voltage electricity.

[0089] In this case, the lithium metal oxide represented by the above chemical formula 1 is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., and the lithium metal oxide represented by the above chemical formula 2 is LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O 4、 LiNi 0.3 Mn 1.7 O 4、 LiFePO4, LiFe q Mn 1-q PO4, etc., which may be used alone or in combination.

[0090] The positive electrode active material may be included in an amount of 85 parts by weight or more, specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the weight of the positive electrode active layer.

[0091] The positive electrode active layer may further contain a conductive material, a binder, other additives, and the like in addition to the positive electrode active material.

[0092] In this case, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, summer black, graphene, and carbon nanotubes.

[0093] The conductive material may be included in an amount of 0.1 to 5 parts by weight based on the weight of each positive electrode active layer, specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.

[0094] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride (PVDF).

[0095] The binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, based on the weight of each positive electrode active layer.

[0096] The total thickness of the positive electrode active layer is not particularly limited, but may specifically be 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.

[0097] In addition, the positive electrode may use a positive electrode current collector that has high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, those that have been surface-treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, the average thickness of the current collector may be suitably applied to be 3 μm to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.

[0098] Meanwhile, the separator interposed between the positive and negative electrodes of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is one commonly used in the art, specifically, one containing at least one polymer selected from polypropylene, polyethylene, and polyethylene-propylene copolymers having chemical resistance and hydrophobicity may be used. The separator may have a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymer, and in some cases, may have a composite separator formed by coating organic or inorganic particles on a porous polymer substrate with an organic binder. In addition, the separator may have an average pore diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.

[0099] Meanwhile, the lithium secondary battery according to the present invention is not particularly limited, and may be a secondary battery having a form that may include a stack type, a zigzag type, or a zigzag-stack type electrode assembly. As one example, the lithium secondary battery according to the present invention may be a pouch type secondary battery or a prismatic type secondary battery.

[0100] <Method of manufacturing the negative electrode> In one embodiment, the present invention further comprises: Simultaneously applying a first negative electrode slurry including a first carbon-based negative electrode active material and a second negative electrode slurry including a second carbon-based negative electrode active material onto a negative electrode current collector; applying a magnetic field to the applied first and second negative electrode slurries; and drying the first and second negative electrode slurries to which the magnetic field is applied to form a first and second negative electrode active layer, The first carbon-based negative electrode active material includes natural graphite and artificial graphite, The first and second negative electrode active layers each have an alignment degree (OI) of 0.1 to 0.9 of the carbon-based negative electrode active material represented by the following formula 1:

[0101] [Formula 1] OI=I 004 / I 110

[0102] In formula 1, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0103] The method for manufacturing the negative electrode according to the present invention includes applying a negative electrode slurry containing a carbon-based active material onto a negative electrode current collector, applying a magnetic field to the surface of the applied negative electrode slurry to align the carbon-based active material in the negative electrode slurry at a predetermined angle with respect to the surface of the negative electrode current collector, and then drying the negative electrode slurry in which the degree of disorder of the carbon-based active material is reduced to form a negative electrode active layer, thereby manufacturing the negative electrode.

[0104] Here, the step of applying the negative electrode slurries may be performed at once by simultaneously discharging two types of negative electrode slurries onto the negative electrode current collector.

[0105] Specifically, the step of applying the negative electrode slurry may be performed by simultaneously applying a first negative electrode slurry including a first carbon-based negative electrode active material and a second negative electrode slurry including a second carbon-based negative electrode active material onto the negative electrode current collector.

[0106] In this case, the first negative electrode slurry and the second negative electrode slurry may have different compositions. Specifically, the first negative electrode slurry includes a first carbon-based negative electrode active material, and the second negative electrode slurry includes a second carbon-based negative electrode active material. In this case, the first carbon-based active material and the second carbon-based active material include at least one type of graphite-based carbon selected from natural graphite and artificial graphite, and the type and content / content ratio of the graphite-based carbon included in each carbon-based active material may be different.

[0107] As one example, the first carbon-based negative electrode active material may include natural graphite and artificial graphite, and the second carbon-based negative electrode active material may include only artificial graphite.

[0108] The particle shape, average particle size, and other characteristics of the natural graphite and the artificial graphite are the same as those described above, and therefore detailed description thereof will be omitted.

[0109] In addition, the steps of applying the first negative electrode slurry and the second negative electrode slurry may be performed by any method commonly used in the art without any particular limitation, for example, the application may be performed by a dip coating, die coating, comma coating, gravure coating, or bar coating method, and preferably by die coating using a dual slot die.

[0110] In addition, the step of applying a magnetic field to the first and second negative electrode slurries may be a step of aligning a crystal plane of the carbon-based active material contained in each negative electrode slurry to have a predetermined angle with respect to the negative electrode current collector. To this end, the step of applying a magnetic field may be applied to a surface of the negative electrode slurries coated in sequence on the negative electrode current collector, i.e., the exposed surface of the second negative electrode slurry, and the first negative electrode slurry located below the second negative electrode slurry may also have a crystal plane of the carbon-based negative electrode active material aligned at a predetermined angle due to the applied magnetic field.

[0111] Here, the degree of alignment (OI) of the carbon-based active material contained in each of the negative electrode slurries can be adjusted by controlling the strength of the applied magnetic field and the time of exposure to the magnetic field.

[0112] For example, in the step of applying a magnetic field, a magnetic field of 2,000 G (Gauss) to 6,000 G (Gauss) may be applied, specifically, a magnetic field of 2,500 G to 5,500 G, 3,000 G to 5,500 G, 3,500 G to 5,500 G, 4,000 G to 5,500 G, 3,500 G to 4,500 G, or 4,500 G to 5,000 G may be applied.

[0113] Furthermore, the step of applying the magnetic field may be performed for 5 to 60 seconds, specifically for 10 to 60 seconds, 10 to 30 seconds, 30 to 60 seconds, 40 to 50 seconds, 15 to 35 seconds, or 10 to 50 seconds.

[0114] As one example, in the step of applying a magnetic field, a magnetic field of 4,700±100 G may be applied to the negative electrode slurry for 12 to 33 seconds.

[0115] In the present invention, by applying a magnetic field to the second negative electrode slurry with the above-described magnetic field strength and application time in the magnetic field application step, not only the second carbon-based negative electrode active material contained in the second negative electrode slurry but also the first carbon-based active material of the first negative electrode slurry located below the second negative electrode slurry may be aligned at a predetermined angle with respect to the negative electrode current collector.

[0116] In addition, forming the first and second negative electrode active layers may include drying the first and second negative electrode slurries and rolling the dried first and second negative electrode slurries.

[0117] At this time, the step of drying the first and second negative electrode slurries may be performed in any manner that can maintain the alignment of the carbon-based active material contained in the negative electrode active layer, without any particular limitations.

[0118] For example, the drying step may be performed by applying thermal energy to the negative electrode slurry using a hot air dryer, a vacuum oven, or the like to dry the negative electrode slurry.

[0119] In addition, the rolling of the dried negative electrode slurry is a step of increasing the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roll press, etc. Here, the rolling may be performed at a temperature condition higher than room temperature.

[0120] Specifically, rolling can be carried out at a temperature of 50°C to 100°C, more specifically, at a temperature of 60°C to 100°C, 75°C to 100°C, 85°C to 100°C, 50°C to 90°C, 60°C to 80°C, or 65°C to 90°C. Specifically, the rolling may be performed at a rolling speed of 2 m / s to 7 m / s, more specifically, at a rolling speed of 2 m / s to 6.5 m / s, 2 m / s to 6 m / s, 2 m / s to 5.5 m / s, 2 m / s to 5 m / s, 2 m / s to 4.5 m / s, 2 m / s to 4 m / s, 2.5 m / s to 4 m / s, 2.5 m / s to 3.5 m / s, 3.5 m / s to 5 m / s, 5 m / s to 7 m / s, 5.5 m / s to 6.5 m / s, or 6 m / s to 7 m / s. The rolling may be carried out under a pressure condition of 50 MPa to 200 MPa, specifically, under a pressure condition of 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa, or 80 MPa to 140 MPa.

[0121] The present invention can increase the energy density of the negative electrode while minimizing the change in the alignment degree of the carbon-based active material contained in the first negative electrode active layer and the second negative electrode active layer formed by rolling the dried negative electrode slurry under the above-mentioned temperature, speed and / or pressure conditions.

[0122] Meanwhile, the negative electrode slurry may further include a conductive material, a binder, a thickener, and the like in addition to the carbon-based active material, and these may be materials commonly used in the art.

[0123] The present invention will now be described in more detail with reference to examples and experimental examples.

[0124] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0125] <Examples 1 to 4 and Comparative Examples 1 to 2. Production of negative electrodes for lithium secondary batteries> A negative electrode for a lithium secondary battery was manufactured according to the conditions shown in Table 1 below.

[0126] First, natural graphite and artificial graphite were prepared as carbon-based active materials, carbon black was prepared as a conductive material, and carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) were prepared as binders.

[0127] 95 parts by weight of the prepared carbon-based negative electrode active material, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC), and 2.5 parts by weight of styrene-butadiene rubber (SBR) were mixed with water to a solid content of 50% to prepare a first negative electrode slurry and a second negative electrode slurry.

[0128] The first carbon-based negative electrode active material contained in the first negative electrode slurry had (1) particle shape, (2) average particle size, and (3) content in each carbon-based negative electrode active material adjusted as shown in Table 1 below. However, when the particle shape of the carbon-based negative electrode active material was spherical, the sphericity satisfied 0.70 to 0.95. In addition, the second carbon-based negative electrode active material contained in the second negative electrode slurry was the same as the artificial graphite contained in the first carbon-based negative electrode active material.

[0129] After each negative electrode slurry was prepared, the first negative electrode slurry and the second negative electrode slurry were simultaneously cast onto a copper sheet (thickness: 8 μm) being transferred roll-to-roll (transfer speed: 5 m / min) using a dual die coater. At this time, the first negative electrode slurry and the second negative electrode slurry were cast to average thicknesses of 90 μm and 100 μm, respectively, along the transfer direction of the copper sheet.

[0130] A magnetic field of 4,750±50 G was then applied to the surface of the applied second negative electrode slurry for a time period as shown in Table 1 below, and the negative electrode slurry to which the magnetic field was applied was dried with hot air to form a negative electrode active layer. The formed negative electrode active layer was rolled at 50±1°C, a pressure of 100 to 150 MPa, and a transfer speed of 3 m / s to manufacture a negative electrode for a lithium secondary battery.

[0131] [Table 1]

[0132] X-ray diffraction spectroscopy (XRD) was performed on the first and second negative electrode active layers of the manufactured negative electrode to measure the spectra. In this case, the spectrum of the first negative electrode active layer was measured by peeling and removing the second negative electrode active layer after X-ray diffraction spectroscopy (XRD) measurement of the second negative electrode active layer, and X-ray diffraction was measured on the exposed surface of the first negative electrode active layer. The measurement conditions for X-ray diffraction (XRD) were as follows:

[0133] - Target: Cu (Kα line) graphite monochromator -Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree -Measurement area: (1,1,0) plane: 76.5 degrees < 2θ < 78.5 degrees / (0,0,4) plane: 53.5 degrees < 2θ < 56.0 degrees

[0134] From the spectra measured under the above conditions, the average degree of alignment (OI) of each carbon-based active material represented by Formula 1 was calculated. The results are shown in Table 2.

[0135] [Formula 1] OI=I 004 / I 110

[0136] In formula 1, I 004 represents the area of ​​the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

[0137] Separately, for each of the manufactured negative electrodes, three arbitrary points were set within a unit area of ​​10 cm wide and 10 cm long on the surface of the second negative electrode active layer. Then, the CIE color difference meter was measured for the set three points using a spectrophotometer. The average L* value was calculated from the results of the measurements at the three points, and the average deviation of the three points was calculated based on the average L* value to obtain ΔL*. Next, the second negative electrode active layer that had been measured with the CIE color difference meter was peeled off and removed, and the exposed surface of the first negative electrode active layer was measured with the CIE color difference meter in the same manner. The measurement results are shown in Table 2 below.

[0138] [Table 2]

[0139] <Comparative Example 3. Production of negative electrode for lithium secondary battery> A negative electrode for a lithium secondary battery was manufactured in the same manner as in Example 2, except that a magnetic field was not applied after casting the first and second negative electrode slurries.

[0140] The first and second negative electrode active layers of the negative electrodes thus fabricated had carbon-based active material alignment degrees (OI) of 5.41 and 16.87, respectively. The L* and ΔL of the first negative electrode active layer were 43 and 0.4, respectively, and the L* and ΔL of the second negative electrode active layer were 39 and 0.3, respectively.

[0141] <Examples 5 to 8 and Comparative Examples 4 to 6. Production of Lithium Secondary Batteries> The positive electrode active material is LiNi with a particle size of 5 μm. 0.7 Co 0.1 Mn 0.1 Al 0.1O2 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive material and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.

[0142] A separator made of 18 μm polypropylene was interposed between the obtained positive electrode and the negative electrode produced in each of Examples 1 to 4 and Comparative Examples 1 to 3, and the resulting positive electrode was inserted into a case, and then an electrolyte composition was injected to assemble a lithium secondary battery.

[0143] The type of negative electrode applied to each lithium secondary battery is shown in Table 3 below.

[0144] [Table 3]

[0145] <Experimental Example> In order to evaluate i) the adhesive strength between the negative electrode current collector and the negative electrode active layer and ii) the energy density of the negative electrode according to the present invention, the following experiment was carried out.

[0146] a) Evaluation of adhesion between the negative electrode current collector and the negative electrode active layer The negative electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were cut into test pieces having horizontal and vertical lengths of 25 mm and 70 mm, respectively.

[0147] The prepared specimens were attached to a glass plate using double-sided tape, with the current collector facing the glass plate. The specimens attached to the glass plate were then attached to a tensile tester, and the negative electrode active layer of each negative electrode was peeled off at an angle of 90° at a speed of 100 mm / min at 25° C. The peeling force measured in real time was defined as the interfacial adhesion strength between the negative electrode current collector and the negative electrode active layer, and the measurement results are shown in Table 4 below.

[0148] b) Energy density evaluation The negative electrodes produced in Examples 1 to 4 and Comparative Examples 1 to 3 were each cut into 2 cm 2 A hole was drilled to the size of the negative electrode, and constant current charging and discharging was performed by the three-terminal method to measure the charging and discharging capacity. Specifically, the energy density evaluation of each negative electrode was measured by manufacturing a sample battery including each negative electrode as a sample electrode. At this time, the sample battery was designed to have a structure including a laminate in which each negative electrode, a separator, and a counter electrode were laminated, and a reference electrode was separately introduced on the upper part. In addition, the sample battery was applied with a solution in which LiPF6 was dissolved to a concentration of 1M in a mixed solution of ethylene carbonate (EC) and methyl ethyl carbonate (MEC) (EC:MEC=1:2, vol.:vol.) as an electrolyte, metallic lithium was used as the counter electrode and the reference electrode, and a polyethylene microporous membrane was used as the separator.

[0149] The resulting sample battery had a current of 0.2 mA / cm for each negative electrode area. 2 At a constant current of 0 V (V vs. Li / Li + ) and charge to 0.2mA / cm 2 At a constant current of 1V (V vs. Li / Li + After discharging to 0.1 V, the initial charge-discharge efficiency per unit volume of each sample battery was calculated. The calculated results are shown in Table 4 below.

[0150] [Table 4]

[0151] As shown in Table 4, the negative electrode for a lithium secondary battery according to the present invention has a high adhesive strength between the negative electrode current collector and the negative electrode active layer, and has a high energy density. Specifically, the negative electrode prepared in the examples required a peeling force of 35 gf / cm or more to peel the negative electrode current collector from the negative electrode active layer, and was confirmed to have an initial charge / discharge efficiency of 93.6% or more.

[0152] The negative electrode of the embodiment has a structure in which a first negative electrode active layer and a second negative electrode active layer are laminated in order on a negative electrode current collector, the first negative electrode active layer contains artificial graphite and natural graphite as carbon-based negative electrode active materials, and the degree of alignment (OI) of the carbon-based negative electrode active material contained in the first negative electrode active layer is 1st This means that the content of the carbon black and the artificial graphite is adjusted to a specific range, thereby increasing the adhesive strength between the negative electrode current collector and the negative electrode active layer, thereby improving the electrical performance of the negative electrode active layer.

[0153] These results show that the negative electrode for a lithium secondary battery according to the present invention has excellent adhesive strength between the negative electrode current collector and the negative electrode active layer, and has a high energy density.

[0154] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.

[0155] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but can be defined by the claims.

Claims

1. a negative electrode current collector; a first negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a first carbon-based negative electrode active material; and a second negative electrode active layer provided on the first negative electrode active layer and containing a second carbon-based negative electrode active material, The first carbon-based negative electrode active material includes natural graphite and artificial graphite, The first negative electrode active layer and the second negative electrode active layer each have an alignment degree (O.I) of 0.1 to 0.9 of the carbon-based negative electrode active material represented by the following formula 1: [Formula 1] O.I=I 004 / I 110 In Formula 1, I 004 represents the area of ​​the peak indicating the (0,0,4) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD), I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the content of the artificial graphite is more than 50% by weight based on the total weight of the first carbon-based negative electrode active material.

3. The negative electrode for a lithium secondary battery according to claim 1 , wherein the second carbon-based negative electrode active material comprises artificial graphite.

4. Artificial graphite is a scaly particle, 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the natural graphite is in the form of spherical particles.

5. The average particle size of the artificial graphite is 5 μm to 20 μm. The average particle size of the natural graphite is 15 μm to 25 μm, and 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the average particle size of the artificial graphite is smaller than the average particle size of the natural graphite.

6. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the total thickness of the first negative electrode active layer and the second negative electrode active layer is 50 μm to 300 μm.

7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the average thickness of the first negative electrode active layer is 10% to 100% of the average thickness of the second negative electrode active layer.

8. The degree of alignment (O.I) of the second carbon-based negative electrode active material 2nd ) is the degree of alignment (O.I.) of the first carbon-based negative electrode active material 1st 8. The negative electrode for a lithium secondary battery according to claim 1, wherein the ratio of the metal to the total weight of the negative electrode is 10% to 100%.

9. Simultaneously applying a first negative electrode slurry including a first carbon-based negative electrode active material and a second negative electrode slurry including a second carbon-based negative electrode active material onto a negative electrode current collector; applying a magnetic field to the applied first and second negative electrode slurries; and drying the first and second negative electrode slurries to which the magnetic field is applied to form a first and second negative electrode active layer, The first carbon-based negative electrode active material includes natural graphite and artificial graphite, The first negative electrode active layer and the second negative electrode active layer each have an alignment degree (O.I) of 0.1 to 0.9 of a carbon-based negative electrode active material represented by the following formula 1: [Formula 1] O.I=I 004 / I 110 In Formula 1, I 004 represents the area of ​​the peak indicating the (0,0,4) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD), I 110 represents the area of ​​the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).

10. The method for producing a negative electrode for a lithium secondary battery according to claim 9, wherein a magnetic field of 2,000 G to 6,000 G is applied in the step of applying a magnetic field.

11. The method of claim 9, wherein the applying of the magnetic field is performed for 5 to 60 seconds.

12. The step of forming the first negative electrode active layer and the second negative electrode active layer includes: drying the first negative electrode slurry and the second negative electrode slurry; and rolling the dried first and second negative electrode slurries.

Citation Information

Patent Citations

  • Negative electrode active material and lithium secondary battery containing the same

    JP2016532241A

  • Negative electrode for non-aqueous electrolyte secondary battery and production method for same

    WO2012001845A1